Osteopathy and the treatment of horses - Pusey, Anthony , 1951-2007; Brooks, Julia , 1960-; Jenks, Annabel (Wiley-Blackwell, 2010)
"A clinically-orientated text providing comprehensive information on the rationale, procedures and practice of effective and safe osteopathy on horses. Osteopathy and the Treatment of Horses is a much-needed resource written by a number of leading specialists in the field. This comprehensive text presents the scientific basis of how osteopathy works in animals, as well as providing a working guide to the technical skills needed to perform osteopathic procedures. Drawing on well established practices for humans this book provides details on the full variety of diagnostic and therapeutic osteopathic procedures that can be applied to horses. Demonstrates how professionals treating equine locomotor problems can adapt different procedures in different clinical settings. Covers both treatment with and without sedation and general anaesthetic"--Provided by publisher